Socio-economic benefits of la campagne tropicana beach resort to the host community / Tijani Nasiru Olawale ... [et al.] - Tijani, Nasiru Olawale; Uch-Ibeabuchi, Chinyere Catherine; Yina, Orga Donald (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The study evaluates the socio-economic contribution of La Campagne Tropica Beach Resort to the host community. Information used for the study was collected with the aid of questionnaire administration, personal observation and interview. Purposive sampling technique was adopted to select 60 indigenes of the community who have attained 28 years of age. The study also revealed that the establishment of La Campagne Tropicana in the study areas has provided enormous socio economic benefits to the host community in terms of employment, infrastructure, income hence the federal government through their respective agencies should invest enormous resources in the establishment of tourist attractions in rural areas and provide enabling environment for the private sector to do so in order to reduce unemployment among the youths.